Fetus-in-Fetus: Our Case Series and Review of the Literature - Aslanabadi, Saeid; Badebarin, Davoud; Baky Fahmy, Mohammad A; Ladan, Amir Hossein; Farhadi, Ebrahim; Zarrintan, Sina (Iranian Journal of Pediatric Surgery, 2021)
Fetus in fetu is a rare condition commonly presenting as an epitomized pedunculated vertebrated fetiform mass in a newborn infant. Different kinds of presentation and locations have been reported in the hosts. Although numbers of instances have been reported the fascination and curiosity about other presentations and genesis of fetus in fetu remains confirmed. In Tabriz pediatric surgery ward we have had five different presentations of fetus in fetu. The aim of this case series and a subtle literature review is gathering these interesting presentations.